Effects of active or passive recovery modalities between two 100-m kayak ergometer time trials in the heat on thermoregulatory strain and performance in elite kayakers - Borne, R.; Hausswirth, C.; Bieuzen, F. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In hot environmental conditions, humans decrease their capacity to perform time trial exercise. In order to limit the body temperature increase induced by the heat, pre- and/or post-cooling technics such as cooling vest wearing are commonly used by athletes and present positive results [1]. Furthermore, active recovery is a regular modality used by kayakers between races. However, in the heat, active recovery could induce a sustained thermoregulatory strain, which could have an adverse effect on homeostasis restoration. The purpose of this study is to compare the effects of cooling vest wearing combined with either passive with low frequency electromyostimulation (PASLFES) or active recoveries (AR) between two 1000-m kayak time trials. We hypothesized that negative effects of AR compared to PASLFES could be delayed with cooling vest wearing in hot condition. Methods: Eight elite kayakers completed two sessions of two 1000-m time trials on a kayak ergometer separated by a 75-min recovery period with either AR or PASLFES combined with cooling vest wearing. All the protocol was conducted in the heat but subjects were non-acclimated. Performance time was recorded during each 1000-m. Body temperature was calculated from core and skin temperature measured by thermic pill and thermal camera, respectively. Subjects were asked to rate their perception of thermal sensation on a -3 to +3 scale. They also had to evaluate the recovery intervention (efficacy, sensation) by using a 0 to 10 scale. Results: The AR modality presents the most important decline in time-trial performance (pre- AR: +6.7-s; pre-PASLFES: +2.1-s). The greatest increase in blood lactate clearance occurring during AR (AR-30min: 1.92-mmol/L; PASLFES-30min: 3.9-mmol/L). There is no significant difference between the AR and PASLFES interventions for body temperature at the end of the recovery (pre-AR: +0.1°C; pre-PASLFES: +0.3°C). The PASLFES recovery induces a lower heat sensation than AR. The means perceptions of recovery indicate a better positive effect induced by passive recovery. Conclusion Results of this study suggest that an efficient postcooling recovery can limit the additional thermal strain induced by AR, in hot environment. However, the benefits on performance restoration induced by AR are not as important as with PASLFES recovery, despite a better effect on lactate clearance. This could be partly explained by positive passive recovery effects obtained on subjective parameters such as the feeling of recovery, which might help to maintain maximal performance in hot conditions.